Fruits used in two rural communities of the Sierra Madre Oriental region, Mexico to feed captive Myadestes spp. birds for their acclimation - Roldán-Clarà, Blanca; Horta Hinojosa, Rosa Elvia (Ethnobiology and Conservation, 2022)
The diet of wild and captive slate-colored solitaire (Myadestes unicolor) and brown-backed solitaire (M. occidentalis) had not been studied before. In the Sierra Madre Oriental region in México, people from rural communities involved in the capture, maintenance in captivity, and sale of these birds (known as pajareros) have ethnobotanical knowledge of fruits that provide food for wild populations of solitaires, which they also use to feed the birds during their acclimation in captivity. To contribute to the biological knowledge of these birds, we identified the fruits used by bird keepers for feeding captured solitaires during their acclimation. Using ethnobiological methods, in August 2016 and June 2017 we identified the fruits through guided tours and informal conversations in the rural communities of Roca de Oro, Veracruz, and Amixtlan, Puebla, and defined the bird trader’s socioeconomic profiles through interviews held in 2013 and 2016. Fruits were identified in interviews and by collection of plants during field exploration guided by key informants, including four bird-capturer men and one bird-keeping woman at each community. 23 families, 32 genera, and 36 species of plants, most of them native, were used. The information about the diet of these little studied Neotropical bird species is part of the traditional ecological knowledge of local people and contributes to the nutritional biology of wild populations of solitaires.